Mempelajari Al-Qur’an sebagai Sumber Hukum Melalui Muhkam dan Mutasyabih - Amrain, Deefa Augista; Ihsan HB, Muh. Nur; Miswar, Andi; Sohrah, Sohrah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
This is a reminder for all beings, from Allah, the Creator of the heavens and the earth, the One who sent down the Qur'an to His servants. With this holy book, which is well-clarified with an explicit verse Allah SWT set forth the principals to a religion for mankind, the faith that he ensured people held and to which path they should walk on. In so many clear or muhkam verses, the Qur'an itself is bayan (explanation) and hudan (guidance). Moreover, the Qur'an is a miracle and greatest piece of literature in human history, its verses are mutasyabih (ambiguous) and they have not been explored or analyzed in depth. This research is a literature review with qualitative method when the researcher refers to various papers to obtain further understanding and registering that muhkam verses are verses whose intentions and definitions are clean and not uncertain and mutasyabih are verses whose intentions and definitions are not certain and require further tracking to search their initial meaning.